(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to determine the effect of using Kahoot-based interactive media on the learning motivation of fourth-grade students in the Islamic Religious Education (PAI) subject at SD Negeri 3 Purwawinangun. The study was motivated by low student learning motivation evidenced by a lack of attention, active participation, and enthusiasm during lessons indicating a need for more interactive and engaging instructional media. A quantitative approach was employed using a quasi-experimental method with a non-equivalent control group design. The sample consisted of 40 students, comprising 21 students in the experimental class and 19 in the control class. Data were collected through learning motivation questionnaires, observation, interviews, documentation, and pre-tests and post-tests. Data analysis involved normality and homogeneity tests, an Independent Samples t-Test, and N-Gain analysis using SPSS version 27. The results indicated that the data were normally distributed and homogeneous. Hypothesis testing yielded a significance value of 0.000 (p < 0.05), demonstrating a significant effect of Kahoot-based interactive media on student learning motivation. The mean post-test score for the experimental class was 78.90, which was higher than that of the control class (69.15).